Major General Vijay Shumsher Rana: A Memorable Figure of the Rana Regime - Thapa, Binod (International Journal of Atharva, 2026)
Major General Vijay Shumsher Jabara was a visionary military officer and diplomat from Nepal during the twilight years of the Rana regime. Born in 1974 B.S. as the youngest son of Prime Minister Mohan Shumsher, he rose to the rank of Major General in his mid-teens, a rare distinction. Educated at the University of Calcutta with a master’s degree in English literature, he became known for his intelligence, refined demeanor, and progressive views. Throughout the 1940s and early 1950s, he played pivotal roles in Nepal’s internal politics, foreign policy initiatives, and economic planning. As Nepal’s first envoy to post-independence India, he laid the groundwork for Nepal-India relations. His untimely death in 2010 B.S. in Delhi marked a profound loss for a nation in transition.